2007
DOI: 10.1002/art.22917
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble C60 fullerene prevents degeneration of articular cartilage in osteoarthritis via down‐regulation of chondrocyte catabolic activity and inhibition of cartilage degeneration during disease development

Abstract: Objective. Studies have shown the roles of oxidative stress in the pathogenesis of osteoarthritis (OA) and induction of chondrocyte senescence during OA progression. The aim of this study was to examine the potential of a strong free-radical scavenger, watersoluble fullerene (C60), as a protective agent against catabolic stress-induced degeneration of articular cartilage in OA, both in vitro and in vivo.Methods. In the presence or absence of C60 (100 M), human chondrocytes were incubated with interleukin-1␤ (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 54 publications
(79 reference statements)
5
63
1
2
Order By: Relevance
“…21,22 We have already demonstrated that water-soluble C60 fullerene, a strong free-radical scavenger, can function as a protective agent against catabolic stress-induced degeneration of articular cartilage in a model of osteoarthritis in vitro and in vivo. 23 Water-soluble C60 significantly reduced articular cartilage degeneration in the osteoarthritis rabbit model. These findings suggest that C60 has the potential to protect against oxygen free radical-induced pathological features in a variety of diseases.…”
Section: Yudoh Et Al Dovepressmentioning
confidence: 92%
“…21,22 We have already demonstrated that water-soluble C60 fullerene, a strong free-radical scavenger, can function as a protective agent against catabolic stress-induced degeneration of articular cartilage in a model of osteoarthritis in vitro and in vivo. 23 Water-soluble C60 significantly reduced articular cartilage degeneration in the osteoarthritis rabbit model. These findings suggest that C60 has the potential to protect against oxygen free radical-induced pathological features in a variety of diseases.…”
Section: Yudoh Et Al Dovepressmentioning
confidence: 92%
“…Mn salen derivatives were investigated as well (88). Along with metal-based SOD mimics, some nonmetallic and, thus far less-efficient compounds, such as nitroxides (140) and fullerenes (181,349), also have been explored. Further, covalently bound porphyrins and nitroxides were studied (160).…”
Section: B Antioxidantsmentioning
confidence: 99%
“…A carboxyfullerene protected the liver against carbon tetrachloride intoxication in rats (129). In an osteoarthritis model, a carboxylated C 60 prevented catabolic-stress-induced production of matrix metalloproteinases 1, 3, and 13, downregulation of matrix production, apoptosis, and premature senescence of human chondrocytes (treated with interleukin-1b) in vitro, and degeneration of articular cartilage in vivo, in rabbit knees (349). By using EPR measurements, Yin et al demonstrated the ROS (singlet oxygen, superoxide, and hydroxyl radical)-scavenging abilities of three water-soluble fullerenes, Gd-fullerenol, fullerenol, and carboxyfullerene (with two malonyl groups).…”
Section: Nonmetal-based Sod Mimicsmentioning
confidence: 99%
“…Several reports indicate that sirtuins may have two important roles -"regulation of cellular metabolism" and "response to cellular stresses (stress tolerance)", which are closely involved in the pathogenesis and pathology of a variety of diseases including stress-induced degenerative diseases such as OA [11][12][13]. Various cellular stresses such as mechanical stress, oxidative stress, inflammation and aging have been recognized as major risk factors for OA, and all sources of stress could affect the regulation of chondrocyte metabolism [5][6][7][8][14][15][16][17]. Altered chondrocyte metabolism and changes in their responses to OA-related stresses are implicated in the creation of an imbalance between catabolic and anabolic reactions, leading to osteoarthritic degeneration of articular cartilage [5,8,17].…”
Section: Introductionmentioning
confidence: 99%